Relasi dan Negosiasi Ideologis dalam Naga Sasra dan Sabuk Inten Karya S.H. Mintardja - Teguh Supriyanto (Humaniora, 2011)
Naga Sasra dan Sabuk Inten--the silat story-- is built based on various ideological confrontation. It is assumed that this text has a close relation with extra situation because in outside the text, the political and social situation was facing similar ideological confrontations. Th eproblems are how ideology play in the artistic structure of the text and how are the relation and negotiation pattern of the ideologies. An artistic space is constructed by semantic fields and a place for seedbed of various ideologies. The dominant odeology is feodalism in a text. Negotiation and relation for ideology can be a way to grashep hegemonic ideology. The myth is the medium to relate capitalistic ideology. In extra-textual, capitalism is hegemonic ideology. The genetics of the text originates from capitalism class.